Anti-bacterial and anti-adherence activity of Enterococcus spp. against Staphylococcus aureus CECT 976 - Zanzan M.; Achemchem F.; Hamadi F.; Latrache H.; Elmoslih A.; Amzil K.; Mimouni R. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
Lactic acid bacteria (LAB) have been associated with dairy products and are generally considered as beneficial microorganisms. They are used to improve the safety and the quality of food products by the production of many substances, such as organic acids, diacetyl, hydrogen peroxide and bacteriocins. Enterococcus spp. are among LAB group widely found in Mediterranean dairy products and they have been used as probiotics and bioprotective cultures in fermentative processes to control the growth of pathogenic bacteria. Moreover, they had the ability to form biofilms offering barriers against the colonization by other bacteria on biotic and abiotic surfaces. However, to our knowledge no study on the use of Enterococcus strains as a positive biofilm to control pathogen’s adhesion on abiotic surfaces was reported. The objective of this study was to use, on one hand, Enterococcus spp. as protective culture in the dairy industry. On the other hand, the use of Enterococcus spp. as positive biofilm against adhesion of Staphylococcus aureus 976 on Stainless steel. The results showed that E. faecium and E. faecalis tested had a large spectrum against Staphylococcus aureus 976, and their abilities to reduce the adhesion of Staphylococcus aureus 976 were more than 2 log UFC/cm².
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)